Role of the Steroid Sulfate Uptake Transporter Soat (Slc10a6) in Adipose Tissue and 3T3-L1 Adipocytes - Karakus, Emre; Schmid, Andreas; Leiting, Silke; Fühler, Bärbel; Schäffler, Andreas; Jakob, Thilo; Geyer, Joachim (Frontiers in Molecular Biosciences, 2022)
In addition to the endocrine and paracrine systems, peripheral tissues such as gonads, skin, and adipose tissue are involved in the intracrine mechanisms responsible for the formation of sex steroids via the transformation of dehydroepiandrosterone and dehydroepiandrosterone sulfate (DHEA/DHEAS) into potent androgenic and estrogenic hormones. Numerous studies have examined the relationship between overweight, central obesity, and plasma levels of DHEA and DHEAS. The sodium-dependent organic anion transporter Soat (Slc10a6) is a plasma membrane uptake transporter for sulfated steroids. Significantly increased expression of Slc10a6 mRNA has been previously described in organs and tissues of lipopolysaccharide (LPS)-treated mice, including white adipose tissue. These findings suggest that Soat plays a role in the supply of steroids in peripheral target tissues. The aim of the present study was to investigate the expression of Soat in adipocytes and its role in adipogenesis. Soat expression was analyzed in mouse white intra-abdominal (WAT), subcutaneous (SAT), and brown (BAT) adipose tissue samples and in murine 3T3-L1 adipocytes. In addition, adipose tissue mass and size of the adipocytes were analyzed in wild-type and Slc10a6-/- knockout mice. Soat expression was detected in mouse WAT, SAT, and BAT by immunofluorescence. The expression of Slc10a6 mRNA was significantly higher in 3T3-L1 adipocytes compared to preadipocytes and was significantly up-regulated by exposure to lipopolysaccharide (LPS). Slc10a6 mRNA levels were also up-regulated in the adipose tissue of LPS-treated mice. In Slc10a6-/- knockout mice, adipocytes increased in size in the WAT and SAT of female mice and in the BAT of male mice suggesting adipocyte hypertrophy. Serum levels of adiponectin, resistin, and leptin were comparable in wild-type and Slc10a6-/- knockout mice. Treatment of 3T3-L1 adipocytes with DHEA significantly reduced lipid accumulation, while DHEAS did not have a significant effect. However, following LPS-induced Soat up-regulation, DHEAS also significantly inhibited lipid accumulation in adipocytes. In conclusion, Soat-mediated import of DHEAS and other sulfated steroids could contribute to the complex pathways of sex steroid intracrinology in adipose tissue. While in cell cultures the Soat-mediated uptake of DHEAS appears to reduce lipid accumulation, in Slc10a6-/- knockout mice the Soat deletion induced adipocyte hyperplasia through hitherto unknown mechanisms.